DISTRIBUSI ALOKASI SUMBER DAYA DALAM RUMAH TANGGA DI INDONESIA: ANAK SEKOLAH ATAU BEKERJA? - Ni Putu, Wiwin Setyari (PIRAMIDA; Vol 9, No. 2 Desember 2013, 2014)
Rotten Kid theorem of Gary Becker asserts that if all members of the family received the gift or income of other household members , then even if there are family members who are selfish , they still will maximize total family income . Thus, the welfare of the family members will not be affected at anyone who holds power in the family because of the assumption of homogeneous preferences (unitary approach) . However, these assumptions can be said to be unrealistic , especially recent studies in collective models show systematic differences between the way men and women distribute its power in the household . This paper tries to analyze the behavior of households in Indonesia in distributing the resources they have, especially in determining the child’s human capital formation . Utilizing data from IFLS4 , it can be said in Indonesian households in general have an allocation system that is unitary approach . Distribution is done together does not depend on who holds the power in it . In particular also an indication that the higher the wife’s education , the better the child’s education and are owned by the decline in the probability of child labor .
Keywords: intrahoushold resources allocation; child human capital; unitary versus collective models